Improving Employee Productivity Through TQM with the Meditating effect of ICR - Werdiavy, Renno; Muhaimin, Abdul Wahib; Maulidah, Silvana (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
Because of the high level of competition, businesses need to have an excellent quality management system, which they may attain through Total Quality Management (TQM), to improve their chances of succeeding in the marketplace. It will benefit the productivity of the company's personnel, who are the primary resource in any activity the organization undertakes. ICR needs to be supported by the deployment of TQM in the organization. This demands the company's employees be prepared to face change and improve the quality of their products and processes. This study aims to investigate the impact of TQM dimensions on employee productivity and the function that ICR plays as a mediator in the connection between TQM and employee productivity. Between the months of January and March of 2022, this investigation was carried out at a cocoa agroindustry company located in Bali. Total sampling, also known as a census, is the method of data collection, and structural equation modeling using partial least squares is the approach selected for data analysis (SEM-PLS). According to the findings, the TQM component has a beneficial impact on staff productivity and helps to promote the effect of change readiness, which acts as a mediator.